The Effectiveness of Program Based on Brainstorming Strategy on Developing Achievement Motivation of Bahraini Gifted Underachievers in the Intermediate Stage - Salman, Sayed Salah Alawi (Journal of Curriculum and Teaching Methodology, 2022)
This study aimed to determine the evaluation of the effectiveness of the training program based on a brainstorming strategy on developing achievement motivation of Bahraini gifted underachievers in Bahrain intermediate schools. The sample of the study consisted of 46 male and female students selected randomly from 110 students from the 9th grade and was divided into two groups of 23 students in each. Underachiever gifted students have been identified based on their school grades in the essential academic subjects and have scored highly in the Raven Progressive Metrics test and Williams Creativity Assessment Packet (Version A). In order to answer the questions of this study, a number of tools were utilized, including the Achievement Motivation Scale, School grades, and the training Program. To verify the results of the study, ANCOVA, MANCOVA, and means comparisons were used. Data analysis revealed that there were statistically significant differences (α ≤ 0.05) between the controlled and experimental groups in favor of the experimental group on the achievement motivation. In addition, there were statistically significant differences (α ≤ 0.05) between both groups on developing achievement motivation for the underachiever gifted students due to gender in favor of females. In contrast, there were no statistically significant differences (α ≤ 0.05) between both groups due to the interaction between participants’ gender and group on developing achievement motivation. In addition, there were no statistically significant differences (α ≤ 0.05) due to gender between both groups in all of the dimensions of achievement motivation scale, except in the dimension of "the ability to take responsibility" for the benefit of females.
Keywords: brainstorming; achievement motivation; gifted underachiever; training program